"If the Americans can do it, so can we": How dinosaur bones shaped German paleontology. (September 2016) - Tamborini, Marco
Between 1909 and 1913, Berlin's Museum für Naturkunde (Berlin Museum of Natural History) unearthed more than 225 tons of fossils in former German East Africa and transported them to Berlin. Among them were the bones of Brachiosaurus brancai, which would eventually become the biggest mounted dinosaur in the world. By analyzing the social and communicative strategies that made this expedition possible, this paper aims to reveal several aspects of natural history knowledge production at the end of the long nineteenth century. Using rhetoric, the director of the Geological–Paleontological Museum in Berlin, Wilhelm von Branca, conducted a highly successful campaign to market the dinosaurs in Prussia and to convince public opinion and the Prussian central state of the value of paleontology. He fired the Prussian imagination and took advantage of the competitive urge to emulate American paleontology and industry. This work examines how his public relations strategies shaped the German biological "landscape" of the first decades of the twentieth century. It asks: when and under what conditions did paleontology successfully appeal to the public? How does communication dictate, shape, and constrain the development of a specific epistemic agenda? And what kind of power do the public and money have?